2010
DOI: 10.1007/s10461-010-9699-7
|View full text |Cite
|
Sign up to set email alerts
|

Concordant and Discordant Reports on Shared Sexual Behaviors and Condom Use Among African American Serodiscordant Couples in Four Cities

Abstract: This paper examines the concordance of reported shared sexual behaviors, including condom use, among 535 heterosexual, African American, serodiscordant couples and identifies factors that might predict discordant reports. Percentages of agreement, Kappa and McNemar’s statistics and conditional probability indices are used to measure concordance. Logistic regression models identify predictors of couples’ discordant sexual reports. Analyses revealed Kappa statistics for reporting anal sex, fellatio and cunniling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Nonetheless, we found substantial agreement on reported sexual behaviors within these partnerships. Compared with other matched-couple studies in North America and Europe, which also reflect participation bias, Kenyan matched couples exhibit similar levels of concordance regarding the date of first sex, 29 the frequency of sex 19,30 and condom use. 1519,31 Another limitation of the study is that, even though high levels of agreement between men’s and women’s reports of sexual behaviors indicate that these are reliable measures, we cannot assess the validity or truthfulness of these reports.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Nonetheless, we found substantial agreement on reported sexual behaviors within these partnerships. Compared with other matched-couple studies in North America and Europe, which also reflect participation bias, Kenyan matched couples exhibit similar levels of concordance regarding the date of first sex, 29 the frequency of sex 19,30 and condom use. 1519,31 Another limitation of the study is that, even though high levels of agreement between men’s and women’s reports of sexual behaviors indicate that these are reliable measures, we cannot assess the validity or truthfulness of these reports.…”
Section: Discussionmentioning
confidence: 61%
“…Studies that include matched nonmarital couples in both North America and Africa often recruited their subjects from STI or other health clinics, thereby selecting “high-risk” couples, in which one or both members had sought treatment for a sexual or reproductive health problem. 1519 A few studies in developed countries used matched nonmarital couples drawn from population-based samples, 20 yet to our knowledge, only one study has collected such data in the developing world. 21 Unfortunately, matched-couple samples identified through population-based samples still suffer from participation bias because couples who agree to participate are likely to have closer, more serious or longer relationships.…”
mentioning
confidence: 99%
“…Several studies have examined this issue by assessing interpartner concordance as a marker of condom self-report validity. These studies have found that independent partner agreement is high for reports of vaginal sex, anal sex, and condom frequency [5962] and this is true specifically among African American couples [63]. Despite this, clinic records or biological endpoints would strengthen these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Between 26% and 91% of cohorts included in this review reported having used sexual agreements [ 56 - 59 ]. Among African-American serodiscordant couples, “couple agreement” in reporting of sexual risk behaviours was consistent [ 60 ]; however, individual partners were found to hold different perceptions of transmission risk [ 61 ]. Among same-sex male couples based in Australia, sexual agreements that included casual serodiscordant partners, or having no agreement, were associated with UAI [ 62 ].…”
Section: Resultsmentioning
confidence: 99%